ProP‐ProP and ProP‐phospholipid interactions determine the subcellular distribution of osmosensing transporter ProP in Escherichia coli. Issue 3 (25th November 2016) - Romantsov, Tatyana; Culham, Doreen E.; Caplan, Tavia; Garner, Jennifer; Hodges, Robert S.; Wood, Janet M.
Summary: Osmosensing transporter ProP protects bacteria from osmotically induced dehydration by mediating the uptake of zwitterionic osmolytes. ProP activity is a sigmoidal function of the osmolality. ProP orthologues share an extended, cytoplasmic C‐terminal domain. Orthologues with and without a C‐terminal, α‐helical coiled‐coil domain respond similarly to the osmolality. ProP concentrates at the poles and septa of Escherichia coli cells in a cardiolipin (CL)‐dependent manner. The roles of phospholipids and the C‐terminal domain in subcellular localization of ProP were explored. Liposome association of peptides representing the C‐terminal domains of ProP orthologues and variants in vitro was compared with subcellular localization of the corresponding orthologues and variants in vivo . In the absence of coiled‐coil formation, the C‐terminal domain bound liposomes and ProP concentrated at the cell poles in a CL‐independent manner. The presence of the coiled‐coil replaced those phenomena with CL‐dependent binding and localization. The effects of amino acid replacements on lipid association of the C‐terminal peptide fully recapitulated their effects on the subcellular localization of ProP. These data suggest that polar localization of ProP results from association of its C‐terminal domain with the anionic lipid‐enriched membrane at the cell poles. The coiled‐coil domain present on only some orthologues renders that phenomenon CL‐dependent. Abstract : Osmosensing transporter ProP mediates osmolyte uptake to protect bacteria from osmotically‐induced dehydration. ProP activity is anionic lipid‐dependent and ProP concentrates at the poles of Escherichia coli cells in a cardiolipin‐dependent manner. This work suggests that polar localization of ProP results from association of its C‐terminal domain with the anionic lipid‐enriched membrane at the cell poles. The coiled‐coil present on only some orthologues renders that phenomenon CL‐dependent.